Pendidikan Non Formal Sebagai Proses Penanaman Nilai-Nilai Pendidikan Karakter pada Anak Usia Dini Melalui Permainan-Permainan Edukatif - Ravika Virnanda; Sherina Siregar; Widya Febriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This article addresses non-formal education as a method of teaching kids moral principles through educational games. The development of pupils with character, quality, morality, and tolerance is aided by non-formal education. The literature research technique is used to acquire data; through data gathering and conclusion drawing, data that has been gathered from various pertinent sources is examined. The findings of the data gathering are acquired with regard to the process of instilling character values in young children via educational games and the function of instructors in the process of instilling character values in young children through non-formal education. The way parents select games for their children and the surroundings around them can have an impact on the development of character education values in young children.